Solidworks : weldments - Kearte, Dean (InfiniteSkills, 2013)
"In this SolidWorks Weldments training video, expert author Dean Kerste will show you how to successfully navigate through the SolidWorks weldment environment. This training course can be used to help you prepare for the Advanced Weldment Certification exam. It is designed for users that already have a fundamental understanding of SolidWorks. You will start out by learning how to create a weldment. Once you have the basics down, Dean goes into more detail, teaching you about groups, corner treatment, and the trimming of structural members. This video tutorial also walks you through how to add plates, end caps, gussets, and weld bead to a weldment of a workbench. Next, you will cover cut lists and how to add them to a drawing. You will finish the workbench model by creating sub-weldments, as well as a new part file from that sub-weldment. You will also learn to create a custom structural member profile and the common mistakes to avoid. Finally, Dean shares his study tips to help you be successful in passing the weldments exam. You will also go through a certification review and be able to test your developed skills with a practice test."--Resource description page.